A portable gas sensor for sensitive CO detection based on quartz-enhanced photoacoustic spectroscopy. (July 2019) - He, Ying; Ma, Yufei; Tong, Yao; Yu, Xin; Tittel, Frank K.
Highlights: A compact, low power consumption, rechargeable CO-QEPAS sensor was demonstrated. A ppb level minimum detection limit shows an excellent sensitivity. The CO concentration from combustion was measured for a practical application. Abstract: A compact, portable and rechargeable sensor platform based on quartz-enhanced photoacoustic spectroscopy (QEPAS) was demonstrated for the sensitive detection of carbon monoxide (CO). The acoustic detection module and the circuit components were both integrated which formed a sensor system with a weight of 3.2 kg and dimensions of 250 × 250 × 50 mm 3 . Water vapor was added to the gas mixture in order to accelerate the vibration translation rate of CO molecules and improve the CO-QEPAS signal performance. An Allan deviation analysis was performed to assess the long-term performance of such a sensor system. For an integration time of 800 s, a minimum detection limit (MDL) of 21 ppb was obtained. To demonstrate the practical application of the reported compact and portable QEPAS sensor, a continuous measurement of CO from the combustion of three kinds of burning materials was performed.